Role of social skills towards job performance: a study on academician in UiTM Cawangan Melaka Campus Bandaraya Melaka - Mohamad Othman, Nurul Syafiqah (2018)
This study is conducted at UiTM Cawangan Melaka Campus Bandaraya Melaka. The main objective of this project paper is to identify role of social skills towards job performance: a study on academician in Uitm Cawangan Melaka Campus Bandaraya Melaka. The independent variables of this study consist of four dimensions under political skill which are social astuteness, networking ability, interpersonal influence and apparent sincerity while, the dependent variable of this study is job performance. The researcher has adopted the descriptive research on the issue. Then, the researchers sampling design is non-probability sampling which is convenience and purposive sampling method with 59 questionnaires were distributed to lecturers among UiTM Cawangan Melaka Campus Bandaraya Melaka. Data were collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The analysis consists the composite reliability, demographic analysis and multiple regression analysis. Based on the findings, the result shows that, the hypothesis testing display only networking ability is accepted, while the other three hypothesis concerning social astuteness, interpersonal influence and apparent sincerity are rejected. In conclusion, it shows that lecturers who adopt political skill in their workplace will ultimately increase their job performance.